2021
DOI: 10.18632/aging.203062
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces chemoresistance of esophageal cancer cells to cisplatin through regulating the lncRNA-EMS/miR-758-3p/WTAP axis

Abstract: Hypoxia contributes significantly to the development of chemoresistance of many malignancies including esophageal cancer (EC). Accumulating studies have indicated that long non-coding RNAs play important roles in chemotherapy resistance. Here, we identified a novel lncRNA-EMS/miR-758-3p/WTAP axis that was involved in hypoxia-mediated chemoresistance to cisplatin in human EC. Hypoxia induced the expressions of lncRNA EMS and WTAP, and reduced the expression of miR-758-3p in EC cell line ECA-109. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…In past decades, cytotoxic chemotherapy has been developed, but has no significant advantages for overcoming drug resistance (62). However, accumulating studies have demonstrated that lncRNAs play important roles in chemotherapy resistance (63,64). PCAT6 facilitated chemoresistance of CC cells to cisplatin via the PCAT6/miR-543/ZEB1 axis (46).…”
Section: Discussionmentioning
confidence: 99%
“…In past decades, cytotoxic chemotherapy has been developed, but has no significant advantages for overcoming drug resistance (62). However, accumulating studies have demonstrated that lncRNAs play important roles in chemotherapy resistance (63,64). PCAT6 facilitated chemoresistance of CC cells to cisplatin via the PCAT6/miR-543/ZEB1 axis (46).…”
Section: Discussionmentioning
confidence: 99%
“…report that hypoxia induces chemoresistance in non-small cell lung cancer (NSCLC) ( 55 ), and Zhu et al. find that cisplatin-resistance in esophageal cancer cells was also enhanced by hypoxic conditions ( 54 ). Of note, hypoxia also promotes paclitaxel-resistance in multiple cancers ( 52 , 53 ), which are supported by our results that hypoxia promoted paclitaxel-resistance in PS-BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that high expression levels of the long noncoding RNA (lncRNA) E2F1 messenger RNA (mRNA) stabilizing factor (EMS), Wilms’ tumor 1-associating protein (WTAP), and low expression levels of miR-758-3p were associated with poorer survival in patients with esophageal cancer. In addition, they demonstrated that the interaction between lncRNA-EMS/miR-758-3p/WTAP might be a potential mechanism for hypoxia-mediated cisplatin resistance in patients with esophageal cancer[ 25 ].…”
Section: Discussionmentioning
confidence: 99%